Analisis Kepuasan Wisatawan Terhadap Objek Ekowisata Pantai Binasi Kecamatan Sorkam Barat Kabupaten Tapanuli Tengah - April Sabdi Marbun; Debora S Purba S Purba (CERED Indonesia Institute, 2021)
This study aims to measure the level of tourist satisfaction with the quality of the ecotourism object at Binasi Beach, West Sorkam District, Central Tapanuli Regency. As well as analyzing the effect of the quality of the Binasi Beach ecotourism object on tourist satisfaction. The sample was determined by purposive sampling method, while data collection was done by giving questionnaires to respondents which contained tourists' perceptions of the quality of Binasi Beach ecotourism objects and tourist satisfaction questionnaires. The results of the analysis of the influence of the Binasi Beach ecotourism object on tourist satisfaction partially show that the Attraction and Leisure Variables have a significant effect on tourist satisfaction. While the variables of facilities, infrastructure and transportation have no significant effect on tourist satisfaction. The comfort variable is the variable that has the biggest influence on tourist satisfaction, while the infrastructure variable is the variable that has the least influence on tourist satisfaction. Meanwhile, the five variables of the quality of the Binasi Beach ecotourism object have a significant effect on tourist satisfaction.